Optimizing Arabic Vocabulary Mastery through Word Wall Media in the Firtalia Group at TMI Al-Amien Prenduan - Namlul Wadi; Munirul Abidin; Fatimah Azzahra (Indo Publishing, 2026)
The fundamental problem faced by members of the